Comparison of efficacy between Kirschner wire and cannulated screw internal fixation after pediatric supracondylar humeral fracture osteotomy - JiaHui Li; Hansheng Deng; Xin Qiu; Zilong Huang; Zhenkun Gu; Yang Chen; Zhaohan Wu; Jingtong Luo; Haoran Feng; Jianlin Chen; Shizhe Liu; Shuaiyin Wang; et al. (BMC Musculoskeletal Disorders)
Abstract Background In post-traumatic cubitus varus osteotomy, conventional internal fixation methods typically involve the use of Kirschner wires (K-wires). Nevertheless, with advancements in medical technology and a growing demand for robust internal fixation, surgeons are increasingly opting for cannulated screws. Despite this trend, controversy remains regarding whether cannulated screws are superior to K-wires, particularly in pediatric patients with open epiphyses. This study aimed to compare the clinical treatment outcomes and complications of K-wires and cannulated screws as internal fixation methods in post-traumatic cubitus varus osteotomy procedure in pediatric patients with open epiphyses. Methods We conducted a retrospective review of surgical treatments administered to pediatric patients with post-traumatic cubitus varus at our institution between 2010 and 2022. A total of 89 pediatric patients meeting the inclusion criteria were categorized into the K-wire (group A, 54 patients) and cannulated screw (group B, 35 patients) groups based on the internal fixation method used during osteotomy. Comparative analyses were performed on demographic characteristics, imaging results, postoperative complications, hospitalization duration, and plaster and internal fixation duration between the groups. Treatment outcomes were assessed using the Mayo Elbow Performance Score (MEPS) and Flynn criteria. Results Compared to pediatric patients in group B, those in group A exhibited shorter durations of plaster (Group A: 46.19 ± 18.44 d, Group B: 49.4 ± 15.74 d) and internal fixation (Group A: 65.48 ± 39.62 d, Group B: 128.14 ± 84.22 d) but an extended hospital stay (Group A: 6.07 ± 1.24 d, Group B: 6.09 ± 1.07 d). On the final follow-up radiographs, significantly smaller humerus-Cobb angles (Group A: 8.64 ± 5.2°, Group B: 8.94 ± 6.65°) and lateral prominence indices (LP) (Group A: 0.34 ± 0.27, Group B: 0.3 ± 0.23) were observed for patients in group A than for those in group B. No significant differences were observed between the two groups in terms of postoperative fixation angle loss (P < 0.05). Additionally, the MEPS scores did not show any statistically significant differences (Group A: 97.78 ± 5.96 points, Group B: 97 ± 6.77 points). During the 6-month follow-up period, no statistically significant differences were observed between the two groups in terms of complications such as scar proliferation, restricted movement, residual deformity, pain, recurrent fractures, and lateral prominence of the epicondyle (P < 0.05). Conclusion For young children with significant growth potential, K-wires demonstrated superior advantages over cannulated screws. Moreover, compared with cannulated screws, K-wires reduce postoperative discomfort and the risk of complications, providing a more reliable safety assurance for selecting K-wires in young children.